Acceptance and Commitment Therapy and Cognitive–Behavioral Therapy as Treatments for Academic Procrastination: A Randomized Controlled Group Session. (January 2017) - Wang, Shuo; Zhou, Ya; Yu, Shi; Ran, Li-Wen; Liu, Xiang-Ping; Chen, Yu-Fei
Objective: This study tested the efficacy of Acceptance and Commitment Therapy (ACT), compared with Cognitive–Behavioral Therapy (CBT), in alleviating academic procrastination. Method: A total of 60 (53.3% male) undergraduates suffering from academic procrastination were randomly assigned to two treatment groups (ACT and CBT) and a control group. The procrastination symptoms and related psychological mechanisms were assessed immediately after the closure of treatment and at 3-month follow-up (FU). Results: Both therapies showed remarkable short-term effects in decreasing procrastination, but ACT had a better long-term effect. Participants achieved self-esteem enhancement through treatment of both ACT and CBT. While ACT significantly decreased negative affect and improved neuroticism, CBT had a stronger effect on time management. Conclusion: The findings suggest that both CBT and ACT are effective interventions for procrastinators but may have different therapeutic mechanisms.